(untitled) (Journal of Economic Research & Business Administration, 2018)
In modern realities, tourism is one of the highly profitable and dynamically developing sectors of the world economy. Kazakhstan, possessing unique natural resources and original culture of the people, has a huge potential for the development of tourism in the international and regional markets.The tourist potential of recreational resources and historical and cultural heritage is considered, which allows the country to integrate into the international tourism market, to achieve a dynamic tourism industry in the country and will ensure sustainable employment growth, stimulate the development of related industries and increase the flow of investment into the domestic economy.The cluster approach, previously used in research, is singled out: in analyzing the competitiveness of the state, region, industry; as the basis of a nation-wide industrial policy; when developing regional development programs; as a basis for stimulating innovation; As a basis for interaction between big and small businesses. The cultural and tourist cluster is reflected, which includes the groups of enterprises concentrated in the region, sharing the specialized tourist infrastructure, labor markets and functional structures of the economy.It is noted that when creating a cultural and tourist cluster the leading role belongs to large tour operator firms that provide services outside the country, there are also various tourist agencies, enterprises for accommodation, food, transportation of tourists, provision of related services and production of tourist demand goods.Mechanisms are provided for strengthening state support for the tourism sector, contributing to the development of regions and rural areas of six cultural and tourist clusters with a competitive tourism business, developing forms of public-private partnership in this area.